1996
DOI: 10.1128/jvi.70.2.976-984.1996
|View full text |Cite
|
Sign up to set email alerts
|

The spontaneous reactivation function of the herpes simplex virus type 1 LAT gene resides completely within the first 1.5 kilobases of the 8.3-kilobase primary transcript

Abstract: The herpes simplex virus type 1 (HSV-1) latency-associated transcript (LAT) gene is essential for efficient spontaneous reactivation of HSV-1 from latency. We report here that although the LAT gene is 8.3 kb in length, the first 1.5 kb of the LAT gene alone is sufficient for wild-type levels of spontaneous reactivation. We began with a LAT deletion mutant of HSV-1 strain McKrae in which the LAT promoter and the first 1.6 kb of the 5 end of the LAT gene had been deleted from both copies of LAT (one in each vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
86
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 45 publications
6
86
0
Order By: Relevance
“…LAT is the only viral gene product abundantly expressed in latently infected neurons and thus was an important comparison to wt LAT +/+ HSV-1 [34]. The dLAT2903 mutant virus used for this study contains a deletion from -161 to +1667 relative to the start of the primary 8.3-kb LAT: consequently, dLAT2903 does not express detectable levels of LAT, and reactivation from latency in rabbits and mice is significantly reduced [34][35][36][37]. The LAT -/mutant (dLAT2903) was marker repaired back to wt (dLAT2903R) and has identical properties as the parental wt McKrae strain of HSV-1 [34, 35]: therefore, dLAT2903R is referred to as wt HSV-1 throughout this study.…”
Section: More Neurons Express β-Catenin In Tg Of Mice Latently Infectmentioning
confidence: 99%
“…LAT is the only viral gene product abundantly expressed in latently infected neurons and thus was an important comparison to wt LAT +/+ HSV-1 [34]. The dLAT2903 mutant virus used for this study contains a deletion from -161 to +1667 relative to the start of the primary 8.3-kb LAT: consequently, dLAT2903 does not express detectable levels of LAT, and reactivation from latency in rabbits and mice is significantly reduced [34][35][36][37]. The LAT -/mutant (dLAT2903) was marker repaired back to wt (dLAT2903R) and has identical properties as the parental wt McKrae strain of HSV-1 [34, 35]: therefore, dLAT2903R is referred to as wt HSV-1 throughout this study.…”
Section: More Neurons Express β-Catenin In Tg Of Mice Latently Infectmentioning
confidence: 99%
“…The parental McKrae virus and all mutants were triple plaque purified and passaged only one or two times prior to use. The construction and properties of dLAT2903, LAT3.3A (previously designated LAT1.5a), and dLAT371 have been previously described (14,17,18).…”
Section: Cells and Virusmentioning
confidence: 99%
“…LAT's function also does not appear to be due to antisense downregulation of the important immediate-early gene ICP0, which LAT overlaps in an antisense direction. We recently showed that the first 1.5 kb of LAT alone is sufficient for wild-type levels of spontaneous reactivation (17). This region does not overlap any portion of any known HSV-1 gene.…”
mentioning
confidence: 99%
See 2 more Smart Citations